PLCγ1/PKCθ and its downstream effectors in cutaneous T-cell lymphoma development and progression. (October 2021) - García-Diaz, Nuria; Casar, Berta; Alonso-Alonso, Ruth; Rodriguez, Marta; Ruso-Julve, Fulgencio; Esteve-Codina, Anna; Gru, Alejandro A; Gut, Marta; Gut, Ivo; Gonzalez-Vela, Carmen; Rodriguez-Peralto, José Luis; Varela, Ignacio; et al.
Abstract : Developing mechanistic rationales can improve the clinical management of cutaneous T-cell lymphomas (CTCL). In the last few years, the use of Next Generation Sequencing (NGS) approaches has revealed a rich landscape of genomic alterations potentially influencing the biology of these entities. In this regard, multiple genetic and biological evidences point at a malignant network of signaling mechanisms, highly influenced by deregulated TCR/PLCγ1 activity, to control the biology of CTCLs. In addition, activated STAT3 is associated with clinical progression, although the specific mechanisms responsible for this have not been fully elucidated. Here we studied PLCγ1-dependent mechanisms that can activate JAK/STAT and control tumor growth and progression. Downstream of PLCγ1, we identified PKCθ (a specific T cell PKC isoform) to mediate JAK/STAT3 activation and control CTCL cell proliferation and viability. In vivo, PKCθ blockage in CTCL cells, impaired tumor development and cells spreading to the liver and the lungs. In light of these results, we sought to identify specific PKCθ downstream effectors, that in addition to JAK/STATs, could help understanding its biological role in CTCL. To this end, we studied PKCθ-dependent transcriptome as well as its protein interactome in CTCL cells. This approach helped detecting a number of hits that can potentially explain STAT3 phosphorylation in CTCL cells (i.e. RACK1), and highlight a number of oncogenic activities controlled by PKCq, like mitochondrial activity (i.e. ASK1, HSPA9) and cytoskeletal regulation (i.e. ARHGAP-19 or CCT4, 5). As a result, this dual approach helped identifying a number of protein effectors and target genes that can participate in important CTCL activities like for example cytokine signaling, mitochondrial activity, TP53, and actin cytoskeleton dynamics. Finally, we took advantage of Nanostring to study the expression of a selection of PKCθ target genes, in a cohort of 81 human MF samples and control inflammatory dermatoses. In this context, PRKCQ (PKCθ) gene expression was significantly upregulated in MF cases vs. controls. Moreover, the expression of target genes like PRKACB (encoding for PKA isoform B) or the lymphocyte specific actin binding LCP1 and LCP1, positively correlated with that of PRKCQ expression in MF cases. On the other hand, genes like FGFR3 and RHOB showed a significant yet inverse correlation with PRKCQ in robust agreement with the data generated in CTCL cells. Overall, the results show a PKCθ gene signature that is significant and differentially expressed amongst different MF cases, at different stages of the disease. Moreover, this signature highlights novel CTCL disease mechanisms with translational potential in diagnosis and targeted therapy. In summary, we have uncover a series of PKCθ-dependent effectors/routes that can play a central role in the biology of CTCLs and help to develop novel approaches to diagnose and treat these malignancies.